OPTIMIZATION OF METHANE PRODUCTION FROM MIXED SUBSTRATES OF COW FAECES AND CARICA SEEDS USING RESPOND SURFACE METHODOLOGY - Sutaryo, Sutaryo; Susanto, Setio; Purnomoadi, Agung; Abeng, Doni; Purwasih, Rita (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Anaerobic digestion (AD) of dairy cow feces (DCF) has low methane production per ton of waste. A strategy to overcome this drawback is to co-digest DCF and carica seed (CS). Currently, CS is still a waste from the candied carica in the syrup industry and is often just thrown away into the environment. This research aims to evaluate the optimal level of combination for methane production from DCF with co-substrates of germinated (CGM) and non-germinated (CNG) CS meal using Respond Surface Methodology (RSM). This research uses a completely randomized design with a factorial pattern consisting of the first factor being CGM and CNG, and the second factor being the combined level of DCF and CS (CGM or CNG. The result showed that utilization of CS can increase significantly (p<0.05) methane production of the final substrate compared to the control (digester treating DCF only). Utilization of CGM as co-substrate with DCF can also increase methane production (p<0.05) compared to CNG. All parameters in the liquid phase were in the normal range for AD. Based on the research results, the optimum point with a desirability value close to 1 was achieved at a ratio of CGM10 and DCF90. CS was proven can be used as a co-substrate with DCF to increase methane production of the final substrate and germination can be used as a method to increase the methane yield of CS.